Gel com naringina combinado à fonoforese reduz biomarcadores inflamatórios e oxidativos após lesão musculoesquelética - Santana, Caroline Bomfim Lemos (2025)
Skeletal muscle injuries are common both in daily life and during exercise. Understanding the local inflammatory cascade and regeneration mechanisms is essential to optimize and accelerate the muscle repair process. Research indicates that natural compounds with antioxidant properties can mitigate the damage caused by the inflammatory process. The study aimed to evaluate the effects of a gel with naringin complexed in β-cyclodextrin combined with phonophoresis on inflammatory and oxidative biomarkers after musculoskeletal injury in rats. The methodology included in silico analyses, including physicochemical characterization and toxicity, in addition to in vivo experiments focused on the quantification of cytokines, oxidative damage (TBARS, SOD and CAT) and histological evaluation. The in silico results showed that, despite limited solubility and bioavailability, naringin has good potential for distribution and action in several biological systems when associated with other techniques. In the in vivo study, the animals were equally divided into five groups (n = 40): control (CTR), muscle injury (LM), therapeutic ultrasound (UTP), gel with naringin complexed in β-cyclodextrin (NAR), and therapeutic ultrasound associated with gel with naringin complexed in β-cyclodextrin (UTP + NAR). The injury was induced in the gastrocnemius muscle by mechanical impact, and treatment was performed at intervals of 2, 12, 24, 48, 72, and 96 hours after injury. After 98 hours, the animals were sacrificed and the injured muscle was collected for biochemical and histological analyses. Regarding proinflammatory cytokine levels, only the UTP + NAR group showed a significant reduction in TNF-α and IL1-β. Regarding oxidative damage and activation of SOD and CAT enzymes, all treated groups showed a reduction in comparison to the LM group, with emphasis on the UTP + NAR group, which presented the best results. Histological analysis revealed intense cellular infiltration and centralized nuclei in the LM group, while the treated groups demonstrated a more evident structural recovery. The association of NAR with phonophoresis proved to be promising in attenuating the inflammatory response and modulating the cellular redox state. These results highlight the effectiveness of NAR as an antioxidant agent in topical formulations, especially when combined with UTP (phonophoresis), opening new possibilities for the development of natural compounds aimed at the treatment of muscle injuries and inflammatory disorders.